Site of struggle, custodian of memory: reimagining the St George's Cathedral complex - Myburgh, Rachel Catherine (School of Architecture, Planning and Geomatics, 2026)
A collective effort from citizens transformed the cathedral into a place which they consider their spiritual home (Weeder, 2020). It has been an integral part of South Africa's transition from minority rule to democracy. The evolution of the buildings over time is significant. I have looked at the buildings as they existed previously as well as in their current form. The happenings in and around these structures is also very important. These buildings are steeped in history not only in form but also in respect of attitude and philosophy. The memory of the people of Cape Town, past and present, guide the research and design process. The buildings do not stand apart from the people but rather converse with them. Photographs, plans, and drawings (of all types), together with its written history inform the sites potential. This tells the story of a place of worship conceived in the time of conquest and colonialism, forged by struggle, and come of age as a custodian of memory.